2009
DOI: 10.1097/aco.0b013e32832e7af6
|View full text |Cite
|
Sign up to set email alerts
|

Role of N-methyl-D-aspartate receptor antagonists in postoperative pain management

Abstract: The co-administration of ketamine and morphine as a mixture is not recommended for postoperative pain relief. As an adjunct in multimodal analgesia, low-dose ketamine infusion and the administration of dextromethorphan may be able to improve postoperative pain status. Memantine exhibits the greatest potency among NMDA receptor antagonists. In future, research should consider the perioperative infusion of ketamine followed by long-term administration of memantine for the prevention of persistent pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 29 publications
1
25
1
2
Order By: Relevance
“…64,65 Suzuki et al 66 observed no decrease in VAS scores when adding epidural ketamine to local anesthetics and plasma ketamine levels were <50 ng/mL, but levels >200 ng/mL were associated with unacceptable adverse effects. 67 Despite the high ketamine doses used in the present study, plasma ketamine levels remained between 20 and 70 ng/mL during the first few hours, and between 70 and 135 ng/mL at 24 and 48 hours. Therefore, we can state that with plasma ketamine levels within the recommended range there were no demonstrable benefits as regards PPP incidence.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…64,65 Suzuki et al 66 observed no decrease in VAS scores when adding epidural ketamine to local anesthetics and plasma ketamine levels were <50 ng/mL, but levels >200 ng/mL were associated with unacceptable adverse effects. 67 Despite the high ketamine doses used in the present study, plasma ketamine levels remained between 20 and 70 ng/mL during the first few hours, and between 70 and 135 ng/mL at 24 and 48 hours. Therefore, we can state that with plasma ketamine levels within the recommended range there were no demonstrable benefits as regards PPP incidence.…”
Section: Discussioncontrasting
confidence: 50%
“…36,67 However, it has recently been suggested that this is a too short period to achieve effective prevention of central sensitization, as the inflammatory response to surgery is considered to reach its peak at 48 hours, and probably lasts throughout the first week. 69,70 In our clinical experience, TEA with opiates is associated with urinary retention and the need to maintain bladder catheterization for >48 hours, and this leads us to limit the duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…61 Memantine (20-30 mgÁday -1 ) is better tolerated, more potent, and more slowly eliminated than ketamine (halflives: 60-80 hr vs 2.5 hr, respectively). 62 Memantine reduces chronic postoperative pain and may have potential as an opioid adjunct for acute postoperative analgesia. 62 Lastly, magnesium (50 mgÁkg -1 preoperatively and 8 mgÁkg -1 Áhr -1 intraoperatively) also appears to act via NMDA receptor antagonism and inhibition of calcium influx.…”
Section: N-methyl-d-aspartate (Nmda) Receptor Antagonistsmentioning
confidence: 99%
“…62 Memantine reduces chronic postoperative pain and may have potential as an opioid adjunct for acute postoperative analgesia. 62 Lastly, magnesium (50 mgÁkg -1 preoperatively and 8 mgÁkg -1 Áhr -1 intraoperatively) also appears to act via NMDA receptor antagonism and inhibition of calcium influx. Some studies have found that it reduces postoperative opioid requirements, 63 although a metaanalysis showed no evidence for its efficacy in decreasing postoperative opioid demand and pain.…”
Section: N-methyl-d-aspartate (Nmda) Receptor Antagonistsmentioning
confidence: 99%
“…39 NMDA receptor antagonists have the ability to modulate pain centrally, and possibly preemptively, by limiting central sensitization. In 2004, a review by McCartney et al 40 determined that blockade of the NMDA receptor has been shown to reduce pain scores and analgesic requirements beyond the known duration of action of the substances investigated (ketamine or dextromethorphan).…”
Section: N-methyl-d-aspartate Receptor Antagonistsmentioning
confidence: 99%